Effects of a low carbohydrate diet on sports performance - Rebić, Nemanja; Ilić, Vladimir; Zlatović, Igor (Akademia Wychowania Fizycznego w Poznaniu)
Although high carbohydrate intake (>60%) is generally recommended for athletes, nowadays many experiments involve a low carbohydrate diet. Carbohydrate restriction leads to significant hormonal changes as well as reduced glucose utilization and increased utilization of free fatty acids and ketone bodies as energy sources. This narrative review aimed to discuss the physiological basis of low carbohydrate ketogenic diets (LCKD) and their both positive and negative effects on body composition, power, strength, aerobic capacity and anaerobic performance of athletes and physically active subjects. We searched and analyzed earlier and recently published papers on the subject. Research results showed that LCKD facilitates a reduction of body mass and fat mass while promoting maintenance of lean body mass (LBM). However, compared to a diet with a high carbohydrate content, it is challenging to increase LBM. Despite significant metabolic changes and increased fat oxidation LCKD did not show clear and convincing effects on endurance ability. While LCKD can preserve endurance performance in sports where intensity does not exceed 65-70% VO2max, it is not superior compared to a diet high in carbohydrates. Also negative effects on aerobic capacity can be manifested, especially in women, which may be related to a lower status and transport of iron and due to the difference in fat oxidation between genders. Reduced availability of glucose, decreased glycolytic enzyme activity and metabolic inefficiency (higher oxygen consumption for fat oxidation compared to glucose oxidation) might impair anaerobic performance where the intensity exceeds 70-80%. It seems that LCKD has no particular effects on maximum strength, power and anaerobic lactate abilities because they depend on the phosphagen energy system.
Keywords: sports performance; low carbohydrate diet; body composition; keto diet